Pattern of adverse effects in patients with nephrotic syndrome on oral prednisolone - S., Shankareswari; B., Jayapriya; V., Balamurugan P.; A., Lourdu Jafrin; K., Geetha (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Nephrotic syndrome is a common illness affecting the paediatric age group and 80% of the idiopathic syndrome is steroid sensitive. Multiple relapses make them vulnerable to the adverse effects of corticosteroids. There is limited literature evidence for the adverse effects of steroids in children with renal pathology. Methods: This descriptive, cross sectional study analyses the adverse effects of oral prednisolone in children and adults with nephrotic syndrome Fifty-five patients with nephrotic syndrome, attending nephrology or paediatric OP, more than 3 years of age and who were on oral prednisolone for a minimum of eight weeks were included in the study. Demographic details, detailed history, lab investigations and ophthalmic examination were done and the results were analysed. Results: Hypertension and behavioural changes were the most common adverse effects followed by dermatological, endocrine and metabolic changes. Infections and gastrointestinal disturbances were more in adults (p <0.05). Short stature was more in children (p< 0.05). There was no abnormality in blood glucose levels and body weight. Hypertension, cushingoid habitus, infections and short stature were statistically less in patients on alternate day prednisolone. But no statistical association could be made between the occurrence of cataract and the pattern of prednisolone use. Conclusions: Adverse effects pattern is different among adults and children. Also, the adverse effects are less with alternate day prednisolone regimen. Long term follow up into their adulthood is needed to analyse the morbidity produced by corticosteroids in these subsets of population.